1981
DOI: 10.1029/jb086ib04p02953
|View full text |Cite
|
Sign up to set email alerts
|

Tillamook Volcanic Series: Further evidence for tectonic rotation of the Oregon Coast Range

Abstract: Paleomagnetic directions from the Eocene Tillamook Volcanic Series of the Oregon Coast Range point 46° clockwise from the expected Eocene field direction. Potassium argon dating of six dikes and flows from this formation yields a mean age of 44.3 ± 0.6 m.y. These results establish that the Oregon coastal block of Simpson and Cox (1977) extends north to the Oregon‐Washington border and that this block has rotated clockwise 46° ± 13° during the past 44 m.y. The block has undergone no detectable north‐south trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(38 citation statements)
references
References 60 publications
1
37
0
Order By: Relevance
“…This observation and the lack of younger accretion-related deformation in the Tillamook area ( Fig. 6) are inconsistent with earlier tectonic models that require large rotation (>50°) of an Oregon Coast Range-sized Siletz terrane during oblique collision (e.g., Magill et al, 1981). However, the uncertainties are large enough to permit some collision-related rotation of the SRV (cf.…”
Section: Html) Folds Are Parallel To Precollision Margin B-b′ Is a mentioning
confidence: 39%
See 2 more Smart Citations
“…This observation and the lack of younger accretion-related deformation in the Tillamook area ( Fig. 6) are inconsistent with earlier tectonic models that require large rotation (>50°) of an Oregon Coast Range-sized Siletz terrane during oblique collision (e.g., Magill et al, 1981). However, the uncertainties are large enough to permit some collision-related rotation of the SRV (cf.…”
Section: Html) Folds Are Parallel To Precollision Margin B-b′ Is a mentioning
confidence: 39%
“…Paleomagnetic sampling with portable drilling equipment was also done during mapping to better understand the timing of tectonic rotation and its relation to suturing of Siletzia to the margin. The paleomagnetic studies (Wells and Coe, 1985;Wells et al, 2000), along with the work of Simpson and Cox (1977) and Magill et al (1981), also provide a magnetic polarity stratigraphy useful for correlation with the time scale.…”
Section: Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It is tacitly assumed that the differential rotation between the Northeast Japan and Southwest Japan arcs is attributed to only the opening of the Japan Sea, so that the both arcs must have been situated within the present Japan Sea area. It was concluded that the Northeast Japan arc rotated counter-clockwise about a northern pivot of both moving arcs, which was also reported from studies on western North America (e.g., Oregon Coast Range, Klamath Mountain) (HEPTONSTALL, 1977;SIMPSON and Cox, 1977;MAGILL et al, 1981). The opening of the Japan Sea was, therefore, described as the "bar room door" mode (or "double door" mode) in which two sea floor basins, Southwest sub-basin and Northeast sub-basin, were concurrently created.…”
mentioning
confidence: 64%
“…Beck and Engebretson [66] reported no net rotation of the Eocene Bremerton volcanic rocks, east of the Olympic Mountains. All paleomagnetic data south and southeast of the Olympic Mountains, including the Blakely Formation, the Humptulips Formation, and many earlier results on Eocene rocks south of the Olympics [67][68][69][70][71][72][73] show a consistent clockwise rotation. A tectonic model that might explain these results is in progress.…”
Section: Tectonic Rotationmentioning
confidence: 99%